Literatur Review : Perkembangan Media Pembelajaran Berbasis ICT (Information and Communication Technologies) dan Tradisional Indonesia Materi Konfigurasi Elektron - Dian Nirwana Harahap (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research focuses on electron configuration material in chemistry learning. This research aims to review the development of learning media on electron configuration in chemistry learning through literature studies. This study is expected to be able to provide information on the extent of the development of ICT-based and Indonesian traditional chemistry learning media in electronic configuration material. This research uses a literature review study method. The literature study was carried out by collecting data from various articles obtained from the Google Scholar database that were relevant to electronic configuration learning material and published in the 2014-2024 time period (the last 10 years). The results of the research show that there has been research development related to ICT-based learning media and Indonesian traditional electronic configuration materials in the last 10 years 2014-2024. Learning media in traditional and ICT-based forms have been studied during this period and both have had an impact on student learning outcomes in electron configuration material.